Reduction of chronic non-specific low back pain: A randomised controlled clinical trial on acupuncture and baclofen - Rastqar Ali; Manaheji Homa; Zaringhalam Jalal; Zaringhalam Maryam (BMC, 2010)
Abstract Background Chronic non-specific low back pain (LBP) is a prevalent (80%) and multi-dimensional illness. This study aims to test whether acupuncture, baclofen, or combined treatment with acupuncture and baclofen alleviates symptoms of non-specific chronic LBP in men. Methods Eight-four (84) men aged 50-60 years with non-specific chronic LBP were randomly assigned to four groups: the baclofen group received only baclofen (30 mg/day); the acupuncture group received only acupuncture at selected acupoints; the acupuncture + baclofen group received combined treatment with acupuncture and baclofen treatments; and the control group received no pain reduction treatment. After five weeks of treatment, visual analogue scale (VAS) and self-reported pain disability with the Roland-Morris Disability Questionnaire (RDQ) were conducted for outcome measures. Results After treatment, the baclofen, acupuncture and acupuncture + baclofen groups all had lower VAS and RDQ scores. Significantly higher reduction and improvement in VAS and RDQ scores were found in the acupuncture and acupuncture + baclofen groups compared to the baclofen group. Conclusion The present study indicates that the combined treatment of acupuncture and baclofen is more effective than baclofen treatment alone to reduce pain in patients with non-specific chronic LBP. Trial registration number ACTRN12609000698279